2013
DOI: 10.1371/journal.pone.0067236
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of EYA1, SIX1 and SIX5 Genes and Strategies for Management of Hearing Loss in Patients with BOR/BO Syndrome

Abstract: BackgroundBranchio-oto-renal (BOR) or branchio-otic (BO) syndrome is one of the most common forms of autosomal dominant syndromic hearing loss. Mutations in EYA1, SIX1 and SIX5 genes have been associated with BOR syndrome. In this study, clinical and genetic analyses were performed in patients with BOR/BO syndrome focusing on auditory manifestations and rehabilitation.MethodsThe audiologic manifestations were reviewed in 10 patients with BOR/BO syndrome. The operative findings and hearing outcome were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…In addition, it has been observed that mutations in the human genes EYA1, SIX1 and SIX5, cause the autosomal dominant syndrome Branchio-Oto-Renal, an early developmental defect characterized by varying combinations of branchial (fistulas, sinuses, and cysts), outer, middle and inner ear, as well as renal anomalies. (Song et al, 2013). The RT-PCR analysis confirms the presence of mRNA of Six1 and Eya1, both possible targets of mmu-miR-200c and mmu-miR-205.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, it has been observed that mutations in the human genes EYA1, SIX1 and SIX5, cause the autosomal dominant syndrome Branchio-Oto-Renal, an early developmental defect characterized by varying combinations of branchial (fistulas, sinuses, and cysts), outer, middle and inner ear, as well as renal anomalies. (Song et al, 2013). The RT-PCR analysis confirms the presence of mRNA of Six1 and Eya1, both possible targets of mmu-miR-200c and mmu-miR-205.…”
Section: Resultsmentioning
confidence: 66%
“…It has been reported that in mouse embryo, miR-10a expression follows a HoxB-like expression pattern with a common regulatory element (Tanzer et al, 2005). According to previous luciferase activity studies, it was suggested that miR-10a could be an inhibitor of the HOXA1 expression in megakaryocytic differentiation (Garzon et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, mutations in SIX1 , SIX5 , or EYA1 can lead to branchio-oto-renal (BOR) syndrome, a developmental disorder defined by hearing loss, bronchial fistulae, and renal anomalies 43 . EYA1 is the most commonly mutated gene in BOR syndrome with currently 14 known mutations located within the ED 11, 44, 45 , which contains both the SIX1 interaction site, as well as its tyrosine phosphatase activity 46 .…”
Section: The Role Of Six1 and Eya In Genetic Syndromesmentioning
confidence: 99%
“…A novel deletion mutation, c.1381delA, was detected in the EYA1 gene, and the patient was heterozygous for this change (Figure 2A). This deletion causes a frameshift of amino acids and results in a truncated protein 43 in South Korea and Japan (Table 1) (10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In contrast, few mutations have been reported before in patients with BOR syndrome in Taiwan, China (Table 1) (7).…”
Section: Resultsmentioning
confidence: 99%